Marine seaweeds (biofertilizer) significance in sustainable agricultural activities: A review. Issue 1 (January 2022) - Zafar, A; Ali, I; Rahayu, F
Abstract: The marine environment provides adaptive conditions for many organisms, such as algae, shellfish, mussels, sponges, corals, and barnacles. There is a range of algae in Pakistan's coastal waters, but, unfortunately, they are not used and are wasted. Efficient use of a valuable natural resource that can increase the efficiency of agricultural operations. Algae are abundant and easily found in a wet environment, either in seawater or freshwater. The seaweed and its products are extensively used in crops cultivation to enhance production systems due to many plant-growth-promoting compounds. It has been traditionally used for the fertilization of the fields since the ancient world. Some seaweeds and auxins, a plant hormone responsible for the vegetative growth and auxin-like compounds, have been found. Algae and their associated compounds can support the onset of seed germination and plant root growth, which applies to temperature, resistance to abiotic stress, and improves plants' ability to absorb nutrients.